2005
DOI: 10.1107/s1744309105036559
|View full text |Cite
|
Sign up to set email alerts
|

Systematic replacement of lysine with glutamine and alanine inEscherichia colimalate synthase G: effect on crystallization

Abstract: Two proposals recommend substitution of surface lysine residues as a means to improve the quality of protein crystals. In proposal I, substitution of lysine by alanine has been suggested to improve crystallization by reducing the entropic cost of ordering flexible side chains at crystal contacts. In proposal II, substitution of lysine by residues more commonly found in crystal contacts, such as glutamine, has been proposed to improve crystallization. 15 lysine residues on the surface of Escherichia coli malate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Sequence comparisons suggest that the larger molecular size of MSG isoforms can be attributed to the presence of one or more insertions (Molina et al 1994;Howard et al 2000;Smith et al 2003), while the conserved segments of the amino acid sequence show only ;18% identity. Crystal structures of MSG from E. coli (Howard et al 2000;Anstrom et al 2003) and from mTB (Smith et al 2003;Anstrom and Remington 2006) have been determined, but unfortunately the resolution of the diffraction data is modest, which limits structure-based drug discovery efforts (Anstrom et al 2005).…”
mentioning
confidence: 99%
“…Sequence comparisons suggest that the larger molecular size of MSG isoforms can be attributed to the presence of one or more insertions (Molina et al 1994;Howard et al 2000;Smith et al 2003), while the conserved segments of the amino acid sequence show only ;18% identity. Crystal structures of MSG from E. coli (Howard et al 2000;Anstrom et al 2003) and from mTB (Smith et al 2003;Anstrom and Remington 2006) have been determined, but unfortunately the resolution of the diffraction data is modest, which limits structure-based drug discovery efforts (Anstrom et al 2005).…”
mentioning
confidence: 99%
“…Crystal contact engineering involving substitution of lysine by arginine, a residue more frequently observed to form crystal contacts, has been already described in the literature 36, 37. This method was demonstrated to be a successful alternative to the SER method: instead of decreasing the size of the entropic barrier, a residue is replaced with another with similar conformation entropy but an increased probability to form noncovalent interactions.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that nuclear translocation was blocked only when both NLS were disabled. To verify the functionality of these NLS in the HCMV pAP, and to determine whether Gln could be used instead of Ala as a more conservative replacement for the NLS Arg and Lys residues (2,8,26,36), WT and the NLS1 Ϫ and NLS2…”
Section: Resultsmentioning
confidence: 99%
“…The NLS1 target sequence in UL80 was knocked out using a recombination cassette, composed of the streptomycin-sensitive RpsL gene linked to the neomycin gene, in plasmid pRpsL-neo (K002; Gene Bridges, Dresden, Germany) and the NLS1 flanking sequences. The RpsL-neomycin cassette was replaced in a second recombination by using a mutagenic double-strand oligonucleotide that changed only the NLS1 coding sequence (i.e., from AAACGCCGTAAG1539 to CAACAGCAGCAA1539), substituting glutamine (Gln) for lysine (Lys) and arginine (Arg) in the original NLS1 amino acid sequence KRRK513 (2,8,26,36). The resulting mutant bacmid is called bHCMV-UL80NLS1 Ϫ .…”
Section: Cells and Transfectionmentioning
confidence: 99%